Sleep stage dynamics in neocortex and hippocampus. Issue 6 (16th April 2018) - Durán, Ernesto; Oyanedel, Carlos N; Niethard, Niels; Inostroza, Marion; Born, Jan
Abstract: Mammalian sleep comprises the stages of slow-wave sleep (SWS) and rapid eye movement (REM) sleep. Additionally, a transition state is often discriminated which in rodents is termed intermediate stage (IS). Although these sleep stages are thought of as unitary phenomena affecting the whole brain in a congruent fashion, recent findings have suggested that sleep stages can also appear locally restricted to specific networks and regions. Here, we compared in rats sleep stages and their transitions between neocortex and hippocampus. We simultaneously recorded the electroencephalogram (EEG) from skull electrodes over frontal and parietal cortex and the local field potential (LFP) from the medial prefrontal cortex and dorsal hippocampus. Results indicate a high congruence in the occurrence of sleep and SWS (>96.5%) at the different recording sites. Congruence was lower for REM sleep (>87%) and lowest for IS (<36.5%). Incongruences occurring at sleep stage transitions were most pronounced for REM sleep which in 36.6 per cent of all epochs started earlier in hippocampal LFP recordings than in the other recordings, with an average interval of 17.2 ± 1.1 s between REM onset in the hippocampal LFP and the parietal EEG ( p < 0.001). Earlier REM onset in the hippocampus was paralleled by a decrease in muscle tone, another hallmark of REM sleep. These findings indicate a region-specific regulation of REM sleep which has clear implications not only for our understanding of the organization of sleep, but possibly also for the functions, e.g. in memory formation, that have been associated with REM sleep.